Survival and reproductive performance of female Glossina morsitans when maintained on the blood of different species of wild mammals - Moloo, S.K.; Grootenhuis, J.G.; Kar, S.K.; Karstad, L. (Wiley, 1988)
ABSTRACT. A study was carried out to determine the effect on the reproductive performance of female Glossina morsitans morsitans Westwood when allowed to feed, in vitro, for 63 days on fresh defibrinated blood of buffalo, bushbuck, cattle, eland, oryx, warthog, waterbuck or wildebeest. There were marginal differences in the survival and reproductive performance between eight different groups of tsetse, 200 per group, when fed on the blood of these mammalian species. When allowed to feed for 14 consecutive days on the blood of buffalo, wildebeest or warthog, the mean number of feeds were 6.2 ± 0.3, 6.5 ± 0.3 and 6.3 ± 0.3, respectively. The mean weight of the bloodmeal taken also did not differ significantly between these three groups. Whereas the protein patterns of the blood plasma of the above eight host animals were different, the protein patterns of the haemolymph from tsetse fed on the blood of these hosts were identical. It is thus concluded that the preference shown by tsetse for some mammalian species investigated here may not be based on any aspect of the nutritional value of their blood.